Structural adjustment and the Barbadian economy. - Downes, Andrew S. (1992)
Discusses the main features of the economic performance of Barbados over the past five years. Outlines the nature of structural adjustment and examines the policy package adopted by the Government. Suggests actions for the economic recovery of Barbados.